Becoming Unburdened: Writing and Revealing the Debt of Heteronormativity. (April 2020) - Stern, Danielle M.
In this essay, I use embodied, autoethnography to transform my fiscal self and disentangle my queer body from my heteronormative body. I position autoethnography and auto/archeology as a privileged orientation/method that must be viewed, practiced, and critiqued as such, even for those of us with some circumscription of marginal identities. I write my "radically specific" narrative not only to improve my own relationship, but also to contribute to feminist, queer bodies of knowing and relating that disrupt heteronormative, middle-class, White domesticity. My goal is to inspire others to simultaneously shed the stigma of financial burdens and challenge heteronormative privilege.